Natural Product Betulin‐Based Insulating Polymer Filler in Organic Solar Cells. Issue 9 (9th June 2022) - Zhang, Qilun; Zhang, Huotian; Wu, Ziang; Wang, Chuanfei; Zhang, Rui; Yang, Chiyuan; Gao, Feng; Fabiano, Simone; Woo, Han Young; Ek, Monica; Liu, Xianjie; Fahlman, Mats
Abstract : Introduction of filler materials into organic solar cells (OSCs) are a promising strategy to improve device performance and thermal/mechanical stability. However, the complex interactions between the state‐of‐the‐art OSC materials and filler require careful selection of filler materials and OSC fabrication to achieve lower cost and improved performance. In this work, the introduction of a natural product betulin‐based insulating polymer as filler in various OSCs is investigated. Donor–acceptor–insulator ternary OSCs are developed with improved open‐circuit voltage ( V oc ) due to decreased trap‐assisted recombination. Furthermore, filler‐induced vertical phase separation due to mismatched surface energy can strongly affect charge collection at the bottom interface and limit the filler ratio. A quasi‐bilayer strategy is used in all‐polymer systems to circumvent this problem. Herein, the variety of filler materials in OSCs to biomass is broadened, and the filler strategy is made a feasible and promising strategy toward highly efficient, eco, and low‐cost OSCs. Abstract : A natural product betulin‐based insulating polymer is used as filler in various organic solar cells (OSCs). Donor–acceptor–insulator ternary OSCs are developed with improved open‐circuit voltage ( V oc ). Herein, the variety of filler materials in OSCs to biomass is broadened, and the filler strategy is made a feasible and promising strategy toward highly efficient, eco, and low‐cost OSCs.